INNOVATIVE APPROACHES TO PERSONNEL MANAGEMENT IN THE HOTEL AND RESTAURANT BUSINESS (INNOVATIVE ECONOMY, 2023)
Huhul O.Ya. INNOVATIVE APPROACHES TO PERSONNEL MANAGEMENT IN THE HOTEL AND RESTAURANT BUSINESSPurpose. The aim of the article is systematization and characterization of innovative approaches to personnel management in the hotel and restaurant business.Methodology of research. A methodological toolkit was used in order to realize the set goal, represented by: the method of systematization, with the help of which the approaches of the studied category were determined and classified; the comparative method necessary to compare the positions of scientists regarding the presentation of views on the use of innovations in personnel management in the studied sector; the method of induction, associated with the accumulation of individual facts, data, with the help of which provisions regarding the content of scientific approaches were formulated.Findings. A number of innovative approaches to personnel management in the hotel and restaurant business were highlighted, including: an approach to personnel management based on stimulating initiatives to increase knowledge, skills, and policy support in the field of service quality improvement; an approach to personnel management based on stimulating creativity in expanding leadership opportunities for innovative management and innovative behaviour; an innovative approach to personnel management in the conditions of the involvement of each employee in the performance of all tasks and functions, aimed at the possibility of creating labour reserves characterized by a high level of mutual substitution (or an approach to personnel management in the conditions of the performance of functions and professional tasks of the "full cycle"); an innovative approach to personnel management, aimed at achieving the goals of sustainable development according to the main components, which affects both the level of efficiency, the image on the national and international markets, and the state of environmental and social security (an approach aimed at achieving the goals of sustainable development). It was determined that the emergence of new challenges and threats of the market and social environment requires the formation and implementation of new approaches that will enable the enterprises of the hotel and restaurant sector to secure a competitive position.Originality. Theoretical aspects, which include types of innovative approaches to personnel management in the hotel and restaurant business, have gained further development.Practical value of this research is due to the fact that the approaches given in the article can be used in improving the personnel policy of hotel and restaurant business enterprises, oriented on innovations, which will facilitate adaptation to the changing environment.
Keywords: innovative approaches; personnel management; hotel and restaurant business; sustainable development; full cycle; stimulation of creativity; expansion of leadership opportunities